Hubungan Antara Efikasi Diri dengan Penyesuaian Diri pada Santri Baru di Pondok Pesantren - Dinanti Yusriani; Muhammad Ali Adriansyah; Netty Dyan Prastika (Contemporary Education Review, 2025)
Adjustment became a problem for new students of Islamic boarding school, especially those who didn’t have experience living in a dorm. This research was conducted to see the correlation between self efficacy and adjustment of the new students in Islamic Boarding School Hidayatullah Berau. This research was done using a quantitative approach. The subjects of this research were 53 new students of Islamic Boarding School Hidayatullah Berau which were chosen using Total Sampling method. The datas were collected using self efficacy scale and adjustment scale. Then, the collected datas were analyzed using pearson correlation product moment method. This research showed that there is a positive and significant correlation between self efficacy and adjustment of the new students in Islamic Boarding School Hidayatullah Berau with the value of calculated r > r table = 0.623 > 0.2706 dan p = 0.000 < 0.05. It means that if someone has high self-efficacy, they have the high ability to adjust, and vice versa